A study on dispersion improvement of active sites on supported metal catalysts - Taş, Enes Emre. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
The current work aims to enhance metal dispersion on supported metal catalysts synthesized via dry impregnation (DI) method by focusing on 10 wt.% Ni/γ-Al2O3 catalysts as a specific example. Impregnated samples underwent calcination at varying temperatures (500°C, 700°C, and 900°C) and subsequent reduction at 800°C for 1 h under pure H2 flow. Dispersion levels were determined by using the static H2 chemisorption method. Additionally, N2 physisorption, Raman, XRD and XPS analyses were performed on selected samples. The study includes the use of γ-Al2O3, precalcined Al2O3 at 920°C, and 1 wt.% La- doped Al2O3 as support materials, for which the PZC values were measured as 8.49, 8.42, and 7.82, respectively, using the salt addition method. pH shift models were utilized to determine the final pH values of impregnated slurry and to adjust the pH of the precursor solution. The behavior of nickel species in the impregnating solutions was modeled based on the changing pH, employing stability constants of potential compounds. Suitable complexing agents were selected according to the support material's surface charge across the pH scale to obtain Ni complexes/chelates. UV-Visible Spectrophotometry was used for the analysis of solutions. Results demonstrate that the surface distribution of metallic Ni is the primary factor determining dispersion levels at calcination temperature of 500°C. Conversely, at 700°C and 900°C, the formation of NiAl2O4 becomes the predominant factor, as confirmed by XPS and XRD analyses. NTA and CA complexes yield the highest dispersion results at lower calcination temperatures (500°C and 700°C), while the EDTA complex exhibits better results for sample calcined at 900°C. The highest dispersion level achieved using the Ni-CA complex for sample calcined at 500°C is 9.2624%, whereas the lowest dispersion is observed with the same support and solution when it is calcined at 900°C, with a dispersion of 2.5622%. These findings indicate that dispersion is influenced by a combination of different factors that should be evaluated holistically.
Keywords: Dispersion.; Metal catalysts.